Class A Orphans (version 2020.5) in the IUPHAR/BPS Guide to Pharmacology Database - Alexander, Stephen P.H.; Battey, Jim; Benson, Helen E.; Benya, Richard V.; Bonner, Tom I.; Davenport, Anthony P.; Dhanachandra Singh, Khuraijam; Eguchi, Satoru; Harmar, Anthony; Holliday, Nick; Jensen, Robert T.; Karnik, Sadashiva; et al. (IUPHAR/BPS Guide to Pharmacology CITE, 2020)
Table 1 lists a number of putative GPCRs identified by NC-IUPHAR [194], for which preliminary evidence for an endogenous ligand has been published, or for which there exists a potential link to a disease, or disorder. These GPCRs have recently been reviewed in detail [150]. The GPCRs in Table 1 are all Class A, rhodopsin-like GPCRs. Class A orphan GPCRs not listed in Table 1 are putative GPCRs with as-yet unidentified endogenous ligands. Table 1: Class A orphan GPCRs with putative endogenous ligands GPR3 GPR4 GPR6 GPR12 GPR15 GPR17 GPR20 GPR22 GPR26 GPR31 GPR34 GPR35 GPR37 GPR39 GPR50 GPR63 GRP65 GPR68 GPR75 GPR84 GPR87 GPR88 GPR132 GPR149 GPR161 GPR183 LGR4 LGR5 LGR6 MAS1 MRGPRD MRGPRX1 MRGPRX2 P2RY10 TAAR2 In addition the orphan receptors GPR18, GPR55 and GPR119 which are reported to respond to endogenous agents analogous to the endogenous cannabinoid ligands have been grouped together (GPR18, GPR55 and GPR119).